Metaphor Used in “To My Dear and Loving Husband” by Anne Bradstreet (Jurnal Pustaka, 2025)
The aims of this study are to find out the types of metaphor used in the poem and to analyse the meaning of metaphors found in the poem To My Dear and Loving Husband by Anne Bradstreet. Metaphor is one part of figurative languages which is the most common and widely used in literary works such as poem. This study used descriptive qualitative to analyse the data. This study used Parera’s theory (2004) to identify the metaphorical type employed in the poem and to interpret the poem's implicit meaning from the reader's perspective. The result showed that 5 from 12 lines of the poem used metaphor which 1 line is anthropomorphic metaphor, and 4 lines are metaphor from abstract to concrete. It can conclude that metaphor from abstract to concrete is the dominant type that used in the poem.